Benzodiazepines and antidepressants: Effects on cognitive and functional decline in Alzheimer's disease and Lewy body dementia (2021)
Objectives: We aim to study the effects of the prescription of benzodiazepines and antidepressants on cognitive and functional decline in older adults living with Alzheimer's disease (AD) and Lewy body dementia (LBD) over a 5‐year follow‐up. Methods: This is a longitudinal analysis of a Norwegian cohort study entitled “The Dementia Study of Western Norway” (DemVest). We included 196 patients newly diagnosed with AD (n = 111) and LBD (n = 85), followed annually for 5 years. Three prescription groups were defined: only benzodiazepines (BZD), only antidepressants (ADep), and the combination of benzodiazepines and antidepressants (BZD‐ADep). Linear mixed‐effects models were conducted to analyze the effect of the defined groups on the outcomes. The outcomes were functional decline, measured by the Rapid Disability Rating Scale—2, and cognition measured with the Mini‐Mental State Examination. Results: Prescription of the combination of benzodiazepines and antidepressants in LBD was associated with faster functional decline. In AD, the prescription of BZD and BZD‐ADep was associated with greater functional deterioration. ADep alone did not show positive or negative significant associations with the studied outcomes. Conclusions: BZD and especially the combination of BZD and ADep are associated with functional decline in AD and LBD and should be used cautiously